Leading towards impactful Islamic social finance: Malaysian experience with the value-based intermediation approach - Mahadi, Nur Farhah; Mohd. Zain, Nor Razinah; Engku Ali, Engku Rabiah Adawiah (IIUM Press, International Islamic University Malaysia, 2019)
With the introduction of Sustainable Development Goals or SDGs in 2015, the notion of sustainability and impactful services give an inspiration to the dual financial services industries in Malaysia. The approaches that are taken by both of Islamic financial services industry (IFSI) and its counterpart conventional financial services industry (CFSI) are almost similar. However, a distinguished approach is introduced by the Central Bank of Malaysia towards IFSI. While Sharīʻah provides holistic objectives in comparison to SDGs, the approach of value-based intermediation (VBI) opens a new pragmatic dimension for IFSI in providing impactful and beneficial services to the public at large. The end results of VBI are placed to reach the holistic objectives of Sharīʻah and in achieving complete sustainability of IFSI. This paper investigates the approach of VBI and its proposed implementation from Sharīʻah perspective. Depending on qualitative investigation, this paper also explores the practices of Islamic banks in applying VBI through Islamic social finance and its impacts. It is found that VBI facilitates Islamic banks to provide impactful services to their customers and other innovative strategies based on Islamic social finance.